Methods of Innovation Approach to Forming Communicative Competence of Future Educators - Adilova Munisa Furkatovna (Genius Publishing Group, 2022)
The article discusses the psychological and pedagogical aspects of the innovative approach to the formation of communicative competence of future pedagogues
Keywords: Educational process; professional training; future teacher; student